Political integration of foreigners: How does foreigners suffrage impact natives' attitudes? - Anna Maria Koukal; Marco Portann (Center for Research in Economics, Management and the Arts (CREMA), 2020)
Today's world is characterized by globalization and international mobility, yet most democratic participation rights are still tied to traditional forms of citizenship. As a consequence, non-citizen are the largest group without franchise. We examine how citizens evaluate and react to the enfranchisement of non-citizens in Switzerland. This paper combines a novel dataset about the enfranchisement process of non-citizens with individual and aggregated data about citizens' attitudes toward non-citizens and their perception of democracy. We find evidence that citizens become more skeptical toward additional migration, yet show a tendency to reduce ethnocentric attitudes toward non-citizens residing in Switzerland and are more satisfied with democracy once non-citizen are granted the right to vote.
Keywords: 330; Migranten; Politische Integration; Wahlrecht; Wahlverhalten; Schweiz